أثر دمج إستراتيجيات تنمية التفكير في تدريس العلوم الرياضية على مهارات اتخاذ القرار أثناء الأداء الحركي لدى طلبة قسم التربية البدنية بكلية الآداب والتربية صبراتة ( دراسة وصفية) (Comprehensive Journal of Science, 2025)
This study aims to investigate the impact of integrating thinking development strategies in teaching sports sciences on decision-making skills during motor performance among Physical Education students at the Faculty of Arts and Education – Sabratha, through a descriptive correlational design. The research employed a descriptive correlational methodology, with the population comprising all students in the department during Spring 2025, and a sample of 130 students. Two main instruments were used: a questionnaire on thinking development strategies in teaching sports sciences and a questionnaire on decision-making skills during motor performance. The instruments’ validity and reliability were confirmed, with Cronbach’s alpha values ranging from 0.87 to 0.91, indicating high internal consistency, Results revealed that students’ perception of thinking strategies was high (75.4%), while their motor decision-making skills scored 77.6%, reflecting a good ability to select appropriate responses, organize performance, and make rapid decisions. Data also indicated a positive relationship between the integration of thinking strategies and decision-making skills, supporting the hypothesis that enhancing strategic and cognitive thinking positively influences motor performance,The study concluded that integrating thinking development strategies in sports sciences courses should be reinforced, alongside implementing practical simulations and exercises to improve decision-making skills. Additionally, training faculty members in modern thinking methods is recommended. These findings can contribute to improving the quality of university sports education and enhancing students’ ability to connect theoretical knowledge with practical performance in motor tasks.
Keywords: Thinking Development Strategies, Sports Sciences, Decision-Making Skills, Motor Performance, Physical Education, Active Learning in Teaching